Effectiveness of Pilates-based exercises on the diastasis recti abdominis in climacteric women: a randomized controlled trial - Silva, Elaine Priscila Garcia; Bortolli, Thainá Tolosa de; Vesentini, Giovana; Marini, Gabriela (ABCS Health Sciences, 2024)
Introduction: Recent studies have related the climacteric period with changes in connective tissue elasticity that may be related to diastasis recti abdominis. Mat Pilates is a method of exercise without impact that currently has more practitioners, due to its satisfactory results. However, there are no studies that evaluate the effectiveness of mat Pilates for women with diastasis recti abdominis. Objective: To evaluate the effectiveness of the mat Pilates program in climacteric women with diastasis recti abdominis. Methods: This randomized single-blinded clinical trial evaluated climacteric women with diastasis recti abdominis. The participants were randomized into the experimental group, which participated in 3 weekly sessions of mat Pilates for 12 weeks for a total of 36 sessions, and the control group (without exercises). The inter-rectus distance was measured with a digital caliper. The G*Power Version 3.1.9.2. software was used for the sample calculation, and the SPSS 20.0 program was used for statistical analysis. Results: The study comprised 21 women, including 10 in the control group and 11 in the experimental group, with mean ages of 54.3 ± 7.1 and 55.3 ± 6.0 years and body mass index values of 28.8 ± 5.5 kg/m2 and 29.9 ± 4.48 kg/m2, respectively. In the experimental group, reductions were observed in all the measures related to diastasis recti abdominis (p<0.05) in the supraumbilical, umbilical, and infra-umbilical regions. Conclusion: The mat Pilates method is effective for reducing diastasis recti abdominis in the climacteric period.